Both Low Blood Glucose and Insufficient Treatment Confer Risk of Neurodevelopmental Impairment in Congenital Hyperinsulinism: A Multinational Cohort Study - Helleskov, Annett; Melikyan, Maria; Globa, Evgenia; Shcherderkina, Inna; Poertner, Fani; Larsen, Anna-Maria; Filipsen, Karen; Brusgaard, Klaus; Christiansen, Charlotte Dahl; Hansen, Lars Kjaersgaard; Christesen, Henrik T. (Frontiers in Endocrinology, 2017)
Background/aims: Congenital hyperinsulinism (CHI) is a heterogeneous disease most frequently caused by KATP-channel (ABCC8 and KCNJ11) mutations, with neonatal or later onset, variable severity, and with focal or diffuse pancreatic involvement as the two major histological types. CHI confers a high risk of neurological impairment, however sparsely studied in larger patient series. We assessed the neurodevelopmental outcome in children with CHI at follow-up in a mixed international cohort. Methods: In two hyperinsulinism expert centers, 75 CHI patients were included (Russian, n= 33, referred non-Scandinavian, treated in Denmark n=27, Scandinavian, n=15). Hospital files were reviewed. At follow-up, neurodevelopmental impairment was defined as Bayley-III or Movement ABC-2 score <5 percentile, Developmental Profile-3 score <70, WISC-IV score <70, blindness, cerebral palsy, or epilepsy. Results: Median (range) age at follow up was 3.7 years (3.3m-18.2y). Neurodevelopmental impairment was seen in 35 (47 %). Impairment was associated with abnormal brain magnetic resonance imaging (MRI); odds ratio (OR) (95% C.I.) 15.0 (3.0-74.3), p=0.001; lowest recorded blood glucose ≤1 mmol/L; OR 3.8 (1.3-11.3), p=0.015, being non-Scandinavian patient, OR 3.8 (1.2-11.9), p=0.023; and treatment delay from first symptom to expert center >5 days; OR 4.0 (1.0-16.6), trend p=0.05. In multivariate analysis (n=31) for early predictors with exclusion of brain MRI, treatment delay from first symptom to expert center >5 days conferred a significantly increased risk of neurodevelopment impairment, adjusted OR (aOR) 15.6 (1.6-146.7), p=0.016, while lowest blood glucose ≤1 mmol/L had a trend towards increased risk, aOR 3.5 (1.1-14.3), p=0.058. No associations for early vs. late disease onset, KATP-channel mutations, disease severity, focal vs. diffuse disease, or age at follow-up were seen in uni- or multivariate analysis. Conclusion: Not only very low blood glucose, but also insufficient treatment as expressed by delay until expert center hospitalization increased the risk of neurodevelopmental impairment. This novel finding calls for improvements in spread of knowledge about CHI among health care personnel and rapid contact with an expert CHI center on suspicion of CHI.